Ipsilateral distal radius fracture with elbow dislocation-a rare entity: report of 3 cases - TV, Ravikumar; Grover, Amit; Gadi, Daksh; Samorekar, Bheemsingh (International Journal of Medicine, 2015)
Introduction: Elbow joint is the second most common joint to dislocate after shoulder. 20 percent of elbow dislocations are associated with fractures. Elbow dislocations are commonly associated with coronoid process, radial head and olecranon fractures. Dislocations of the elbow commonly accompany proximal ulna or radial fracture. Elbow dislocation with a distal radius fracture is rare. In the literature, there are very few case reports highlighting such an injury.We report three cases of ipsilateral closed dislocation at the elbow associated with a closed distal radius fracture presented to us over a period of three years. Elbow dislocation was managed by closed reduction in two cases, and k wiring was required in one case. For distal radius open reduction and internal fixation by a buttress plate was done for two cases, and one was managed conservatively. At 6 months of follow up patients had full range of movement of the elbow joint and complete union of the distal radius fracture.Therefore, clinical and radiological assessment of one joint above and below should be done in every case so that these injuries, although rare, should not be missed. In a case of elbow dislocation, a possibility of a distal radius fracture should be kept in mind. A very high degree of suspicion is required for such cases.